Getting distracted: historical-natural habit? (Itinera, 2024)
This article delves into the phenomenon of distraction as a cluster of habits that underlies the nervous lives of literary modernity and holds a potentially counter-canonical conceptual significance by haunting daily and scientific practices like reading. On one hand, these habits of distraction could be considered as a part, perhaps even the common denominator of those highly routinized activities that may constitute the natural history of the human forms of life. On the other hand, they may serve as a lever to rethink the natural-historical conceptual tradition itself. Starting with an analysis of the thematic and methodological literary relevance of this phenomenological area in Moravia’s major existentialist novels, this article will further explore its philosophical and anthropological importance by contrasting De Martino’s interpretation of Moravia and Benjamin’s idle materialism with Gehlen’s concept of “second nature” as based on James’s psychology and Heidegger’s stigmatization ofeveryday life as inauthentic.
Keywords: Habits of Distraction, Boredom, Natural History, Close Reading